Seguridad vial, un desafío de salud pública en la Colombia del siglo XXI (2009)
ABSTRACT: To review the topic regarding road traffic safety as a challenge to public health in orderto define an intervention and a research framework in the country. Methodology: national and international data was traced back in yearbooks, printed and electronic means, and SciELO\saludpública electronic library. Results: development, extend, and tendencies of the problem, as well as its constitutional, legal and pragmatic framework in Colombia were systematized. Conclusions: the relevance to carry out a systematic research procedure and intervention of the problem in the xxi century Colombia was made evident.